2022
DOI: 10.3390/ijms23158518
|View full text |Cite
|
Sign up to set email alerts
|

miR-199a: A Tumor Suppressor with Noncoding RNA Network and Therapeutic Candidate in Lung Cancer

Abstract: Lung cancer is the leading cause of cancer death worldwide. miR-199a, which has two mature molecules: miR-199a-3p and miR-199a-5p, plays an important biological role in the genesis and development of tumors. We collected recent research results on lung cancer and miR-199a from Google Scholar and PubMed databases. The biological functions of miR-199a in lung cancer are reviewed in detail, and its potential roles in lung cancer diagnosis and treatment are discussed. With miR-199a as the core point and a divergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 135 publications
0
8
0
Order By: Relevance
“… 59 A further example relates to the 2-fold repressed tumour suppressor miR-199a-3p which targets ARG2 . 60 As described above, ARG2 is highly expressed in tumour associated macrophages and its induced expression is unique to cRaf females ( Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 88%
“… 59 A further example relates to the 2-fold repressed tumour suppressor miR-199a-3p which targets ARG2 . 60 As described above, ARG2 is highly expressed in tumour associated macrophages and its induced expression is unique to cRaf females ( Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 88%
“…In the context of NSCLC, miR-199a has been found to be significantly downregulated compared to normal tissue. Previous studies have consistently reported miR-199a as a tumor suppressor in NSCLC, and its reduced expression has been attributed to methylation abnormalities ( Meng et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The numerous lncRNAs produced by human cells have signi cant roles in a number of biological processes, which include genome expression and cell differentiation [28]. Previous work has suggested that irregular lncRNAs expression may have a function in cancer development and evolution [29,30]. It is noteworthy that this is the rst full-scale work on the role of lncRNAs associated with Cuproptosis in WT.…”
Section: Discussionmentioning
confidence: 99%